Talent Management and Transformational Leadership: An Analysis of Their Roles in Organizational Adaptation to Technological Disruption - Muhdar Muhdar (Maneggio, 2026)
Technological disruption driven by artificial intelligence, big data, and automation has reshaped organizational structures, competencies, and competitive dynamics, requiring organizations to strengthen their adaptive capacity. This study aims to analyze the role of talent management and transformational leadership in enhancing organizational adaptation to technological disruption. A quantitative explanatory design was employed using survey data collected from 215 employees in organizations undergoing digital transformation. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationships among talent management, transformational leadership, and organizational adaptation. The results indicate that talent management significantly influences organizational adaptation through digital competency development and reskilling initiatives. Transformational leadership also has a significant positive effect on adaptation by fostering innovation, commitment to change, and psychological readiness. Additionally, talent management significantly strengthens transformational leadership effectiveness. The model explains 62 percent of the variance in organizational adaptation, demonstrating substantial predictive power. The study concludes that the integration of strategic talent management and transformational leadership is essential for building agile, resilient, and digitally responsive organizations in the era of technological disruption.